NIMG-21. VARIABLE RESOLUTION HYPERPOLARIZED [2-13C]PYRUVATE MRI IN HEALTHY VOLUNTEERS AND PATIENTS WITH IDH-MUTANT GLIOMA. (12th November 2021) - Vaziri, Sana; Kim, Yaewon; Autry, Adam; Chen, Hsin-Yu; Gordon, Jeremy; LaFontaine, Marisa; Hu, Jasmine; Lupo, Janine; Clarke, Jennifer; Villanueva-Meyer, Javier; Oberheim-Bush, Nancy Ann; Chang, Susan; et al.
Abstract: INTRODUCTION: Mutations in isocitrate dehydrogenase (IDH) have been investigated as a prognostic biomarker in glioma. The presence of the IDH mutation (IDHm) is associated with 2-hydroxyglutarate (2HG) production and inhibition of glutamate synthesis (McBrayer, Cell 2018). Hyperpolarized carbon-13 (HP- 13 C) MRI enables dynamic measurements of in-vivo metabolism using a [2- 13 C]pyruvate labeled probe that undergoes conversion to [2- 13 C]lactate and [5- 13 C]glutamate. Here, we present HP [2- 13 C]pyruvate data from healthy volunteers and patients with IDHm diffuse glioma. Due to its intrinsic low signal-to-noise ratio (SNR), we demonstrate the ability of post-processing denoising to improve its utility and aid in detection of metabolic changes associated with IDHm. METHODS: Dynamic HP 13 C data were acquired following intravenous injection of [2- 13 C]pyruvate from five healthy volunteers and one patient with IDHm grade III astrocytoma. A novel multi-resolution frequency specific multislice EPI sequence was used to obtain [2- 13 C]pyruvate, [5- 13 C]glutamate, and downfield and upfield [2- 13 C]lactate signals (3s temporal resolution, pyruvate/lactate/glutamate spatial resolutions = 0.75x0.75cm 2 / 2.25x2.25cm 2 / 2.25x2.25cm 2, 5 slices 3cm thick). Following phase correction, patch-based tensor decomposition denoising was applied to metabolite images. Metabolite differences between normal-appearing white matter (NAWM) and T2 lesion were examined for the patient data. RESULTS: HP [2- 13 C]pyruvate imaging is able to simultaneously probe glycolytic ([2- 13 C]lactate) and oxidative ([5- 13 C]glutamate) metabolism. Denoised pyruvate/lactate/glutamate signals achieved a 4-9/3-6/3-7 fold increase in SNR. T2 lesion exhibited decreased glutamate-to-pyruvate and glutamate-to-lactate AUC ratios versus contralateral NAWM (p< 0.018, p < 1.5e-5), consistent with IDH mutant status. CONCLUSION: We successfully demonstrated the feasibility of applying variable resolution HP [2- 13 C]pyruvate metabolic imaging to detect IDHm specific metabolism. This technique addresses a major hurdle in HP 13 C MRI by improving SNR while permitting robust metabolism quantification. Future studies will optimize methods for acquiring and processing data to evaluate further data acquired from IDHm glioma patients. Supported by NIH T32 CA151022, P01 CA118816, and NICO.